Perspektif Implementasi Total Quality Management (TQM) pada Institusi Pendidikan Tinggi - Slamet, Slamet (el Harakah: Jurnal Budaya Islam, 2006)
In realizing the social demand in this turbulent environment and fulfilling the social needs of higher education, the management should consider the quality of education. Therefore, this study intends to adopt the theory of Total Quality Management (TQM), which has been developed and only understood by the managers of business institutions, to be applied in higher education institutions that are responsible for improving the quality of human resources. Although the TQM concept in higher education is still in controversy, this study is expected to give contribution to the creative thought. The realization of total quality, indeed, is easier to discuss than to implement. The implementation of TQM is interesting and binding as well because it insists fundamental change and reform of the culture of traditional organization. Besides, it also insists commitment and totality that must be realized seriously. Human resources as the vital components in higher education must be paid attention and treatment as insisted by TQM requirements, that is, cross-functional cooperation, empowerment and involvement of all staffs, participative management style, availability of effective media of communication and others. Dalam mewujudkan permintaan sosial di lingkungan yang penuh gejolak ini dan memenuhi kebutuhan sosial pendidikan tinggi, manajemen harus memperhatikan kualitas pendidikan. Oleh karena itu, penelitian ini bertujuan untuk mengadopsi teori Total Quality Management (TQM), yang telah dikembangkan dan hanya dipahami oleh para pengelola lembaga bisnis, untuk diterapkan di institusi pendidikan tinggi yang bertanggung jawab atas peningkatan kualitas sumber daya manusia. Meski konsep TQM di perguruan tinggi masih dalam kontroversi, penelitian ini diharapkan dapat memberikan kontribusi terhadap pemikiran kreatif. Realisasi kualitas total memang lebih mudah dibahas daripada diimplementasikan. Implementasi TQM juga menarik dan mengikat karena ini menegaskan perubahan mendasar dan reformasi budaya organisasi tradisional. Selain itu, ia juga menegaskan komitmen dan totalitas yang harus diwujudkan dengan serius. Sumber daya manusia sebagai komponen vital dalam pendidikan tinggi harus diperhatikan dan diperlakukan sesuai dengan persyaratan TQM, yaitu kerjasama lintas fungsi, pemberdayaan dan keterlibatan semua staf, gaya manajemen partisipatif, tersedianya media komunikasi yang efektif dan lainnya.